First record of Mantibaria Kirby, 1900 (Hymenoptera, Scelionidae, Scelioninae) in the New World: a probable case of accidental introduction - Oliveira, Bruno Garcia De; Schoeninnger, Karine (Zootaxa, 2017)
Mantibaria Kirby, 1900 has four valid species: M. seefelderiana (De Stefani), M. mantis (Dodd), M. solygiea Risbec and M. kerouaci Veenakumari & Rajmohana. It is found in the Palaearctic, Afro-tropical, Oriental and Australian regions, and now is known from the New World. There are some taxonomic barriers that hinder the understanding and the boundaries between the four species, some of which were discussed by Masner (1976), Mineo (1980) and Galloway & Austin (1984). These authors argued that there are no reliable differences to separate M. solygiea (Europe), M. seefelderiana (= M. anomala, Africa) and M. mantis (Australia), hypothesizing that these three species actually comprise only one species that is widely distributed in the Old World.